Perceived Benefits of Kinesio Tape® Compared to Non-Kinesiology Tape and No Tape in Healthy Collegiate Athletes - Gregory Chown; Jennifer Innamorato; Marlee McNerney; Jennifer Petrilla; Hillary Prozzillo (Scholarworks @ WMU, 2016)
Background: Sports participation is considered a meaningful occupation for people of all ages. Multiple disciplines use Kinesio Tape® during treatment (Kinesio Taping® Association International, 2013e) for sportsrelated injuries. While the use of Kinesio Tape® is becoming increasingly popular in sports, there is a lack of evidence supporting its effectiveness. The purpose of this study was to address the following question: Is there a perceived sports performance benefit of using Kinesio Tape® compared to non-kinesiology tape or no tape in healthy collegiate athletes? Method: This quantitative pilot study used a convenience sampling method. The participants included eighteen healthy men's and women's lacrosse players from a division III university. A crossover design was used and consisted of three trials: Kinesio Tape®, non-kinesiology tape, and no tape. Perceived sports performance was measured using an 8-item, study-specific questionnaire. Results: The results indicated that there were no significant differences between the Kinesio Tape® and no tape trials. There were statistically significant differences found between the non-kinesiology tape and no tape trials. Conclusion: While non-kinesiology tape was the only tape that yielded significant differences, the participants perceived their sports performance to be better when wearing either non-kinesiology tape or KT than when wearing no tape, indicating a possible placebo effect.